Dimensi Kepemimpinan dalam Al-Qur'an - Aghnia Faradits (At-Tahfidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
This paper focuses on discussing issues of non-Muslim leadership in the context of inter-religious relations. This problem is felt by almost the entire world, especially countries where there is religious pluralism that carries out socio-political-religious relations side by side, like Indonesia. The problem that occurs is the result of the polemic on the issue of non-Muslim leadership which was ratified by the state constitution but not in the religious constitution (read: for some). It is at this point that this paper aims to find a solution to it. The author in this study presumably uses a philosophical-historical approach, or more on the aspects of the socio-social approach, namely an approach that places the Koran (QS Ali Imran verse 28, 118 and QS Al-Maidah verse 51) as a formal object while the socio-social context. community as the material object of focus (in this case the author focuses on the problem of leadership in Indonesia).